THE INFLUENCES OF THE CULTURAL MODELS ON AGRICULTURAL PRODUCTION STRUCTURES IN ROMANIA AND SOME EU-28 COUNTRIES - A PERSPECTIVE - Jean Vasile, Andrei; Dusmanescu, Dorel; Mihai, Mieila (Economics of Agriculture, 2015)
The evolution of the Common Agricultural Policy and the changing of its paradigm was a subject of extensive consideration in the literature, but never the implications of specifc cultural aspects on agricultural performance and production structures were ever taken into consideration. The main aim of the paper is the analysis of the some aspects regarding the influences of the cultural models on agricultural production structures in Romania and some EU- 28 countries, form a larger perspective, starting with the CAP transformations over the time and the European agricultural model, analysing the role of the multifunctional agriculture in shaping the holdings structure and performances, and in the last it is considered the role of agriculture and rural communities in promoting renewable including bio-fuels.